Potential risk assessment of miR-143 gene polymorphisms rs41291957 and rs353292 in colorectal cancer - Ahmed, Mehvish Naseer; Mansoor, Qaisar; Baig, Ruqia Mehmood; Tahir, Tehreem; Abbasi, Samina Asghar (Cellular and Molecular Biology, 2020)
Colorectal cancer is a life-threatening and therapeutically challenging disease. Increasingly it is being deciphered that genetic and epigenetic mutations play a central role in cancer onset and progression. Excitingly, discovery of non-coding RNAs is considered to be a milestone in molecular oncology and emerging evidence is deepening our understanding about pivotal role of miRNAs in carcinogenesis. miR-143 has been experimentally verified to play an instrumental role as tumor suppressor. Recent studies suggest that single nucleotide polymorphisms rs41291957 and rs353292 in miR-143 may associate with the progression and or development of colorectal cancer. In present study 400 Pakistani subjects participated including 200 colorectal cancer patients and 200 age and gender matched healthy individuals. Blood samples and clinical information of the confirmed patients was collected from cancer diagnosis and treatment hospitals in Pakistan. The polymorphisms rs41291957 and rs353292 were genotyped in patients and controls by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and results were validated by Sanger sequencing. The association of the SNPs within the study group was analyzed by Ï‡² test with p value < 0.05 as significant. Odds ratio was calculated with 95% confidence interval.Genetic predisposition to cancer was observed in presence of characteristic rs45291957 polymorphism. Ï‡² test results show strongly significant association mi-RNA rs45291957 SNP with colorectal cancer p value 0.0111 (<0.05) along with the statistically significant correlation tested by odds ratio with 95% confidence interval. However, no significant correlation (p value 0.6683) could be found for the association of rs353292 with colorectal cancer in Pakistani population. The present study for the first time gave evidence of miR-143 rs41291957 involvement in colorectal cancer patients of Pakistani population. This target can be a useful molecular tool for the prognosis and treatment targets for colorectal cancer in Pakistani population. rs353292 genetic association can be explored for different cancers in Pakistan to completely rule out its role in cancer.